Retailing: Emerging Challenges and Future Prospects In India. - Radha, Anu (International Journal of Scientific Research and Management (IJSRM), 2014)
The Indian retail industry has been thrown open to foreign majors and is packed with players who strive tooffer great products and value-for-money to Indian consumers. The country holds a vast promise forretailers with its burgeoning spending power and a rising middle class.The organized retail segment is in its nascent stage and has a huge potential to harness in the subcontinent.Foreign giants like Wal-Mart and IKEA have recently received the Government’s nod to enterinto the Indian market, after making all the necessary compliances.This research paper provides the current status of the retail sector in India and the detailed informationabout the challenges faced by the retail sector in India. The paper includes the opportunities of retail stores,retail format in India and the recent trends in retail. This paper surveys the managers to understand thechallenges impacting the retail sector. It concludes with providing the detailed opportunities available forthe retail sector.